Urgensi Manajemen Mutu Pendidikan Dalam Meningkatkan Akreditasi Di Smk Bina Insan Mandiri Kota Cirebon - Wahyono Wahyono; Aulia Rahma (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2026)
This research aims to find out how quality management in improving accreditation in schools. This research method uses a descriptive qualitative approach using interviews, observation, and documentation as data collection techniques. The results showed that (1) Planning of education quality management at Bina Insan Mandiri Vocational School in Cirebon City is said to be good and has accreditation B which is able to manage the quality of school education. (2) Organizing in improving accreditation at SMK Bina Insan Mandiri Cirebon City has been implemented. (3) Directing education quality management in improving accreditation at Bina Insan Mandiri Vocational School in Cirebon City has been implemented well. (4) Controlling education quality management in improving accreditation at Bina Insan Mandiri Vocational School in Cirebon City has been carried out well. Keywords: Management, Education Quality, Accreditation